2016
DOI: 10.1016/j.renene.2016.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of latent heat thermal energy storage using encapsulated phase change material for solar thermal power plant

Abstract: 6Thermal energy storage improves the load stability and efficiency of solar thermal 7 power plants by reducing fluctuations and intermittency inherent to solar radiation. This paper 8 presents a numerical study on the transient response of packed bed latent heat thermal energy 9 storage system in removing fluctuations in the heat transfer fluid (HTF) temperature during the 10 charging and discharging period. The packed bed consisting of spherical shaped encapsulated 11 phase change materials (PCMs) is integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(33 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…Over the past decade, comprehensive research work has been conducted on the packed bed latent heat thermal energy storage system (PBTES) employing spherical PCM capsules having the same diameter to examine the thermal performance by estimating the charging time and the first law efficiency . Xu et al provided an elaborate review of PCM along with thermal performance enhancement techniques suitable for TES for CSP plants.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, comprehensive research work has been conducted on the packed bed latent heat thermal energy storage system (PBTES) employing spherical PCM capsules having the same diameter to examine the thermal performance by estimating the charging time and the first law efficiency . Xu et al provided an elaborate review of PCM along with thermal performance enhancement techniques suitable for TES for CSP plants.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Methods for LHS performance enhancement include extending heat transfer surface, [13][14][15][16][17][18][19] improving process uniformity 7,20 and enhancing PCM conductivity. [9][10][11][12] Methods for LHS performance enhancement include extending heat transfer surface, [13][14][15][16][17][18][19] improving process uniformity 7,20 and enhancing PCM conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Methods for LHS performance enhancement include extending heat transfer surface, [13][14][15][16][17][18][19] improving process uniformity 7,20 and enhancing PCM conductivity. [15][16][17] Saghir and Bayomy 18 investigated a ternary mixture of water with a nanofluid and a microencapsulated PCM in a porous medium. Their results indicated a limited improvement of the thermal performance.…”
Section: Introductionmentioning
confidence: 99%
“…A high‐temperature solar thermal energy storage unit based on the molten soda lime silica glass was examined by Cárdenas et al They demonstrated that the overall performance of the thermal energy storage unit was satisfactory and the unit was capable of supplying the required 4 kW output throughout the 16‐hour discharge while it reached its fully charged state during the subsequent 8‐hour recharge. The analysis of latent heat thermal energy storage using the encapsulated PCM for solar thermal power plant was carried out by Bhagat and Saha . They showed that the ability of the latent heat thermal energy storage system to store and release energy was significantly improved by increasing mass flow rate and inlet charging temperature.…”
Section: Introductionmentioning
confidence: 99%